(untitled) (Tanzania Medical Journal, 2025)
Background: Women's participation in water, sanitation, and hygiene (WASH) related projects is crucial for promoting public health and achieving sustainable development. However, in many rural settings, women remain underrepresented in WASH-related decision-making bodies and committees. Socio-economic constraints, including low income, high levels of illiteracy, unequal power relations, and heavy domestic workloads, continue to limit women’s meaningful engagement. This study explored women’s participation in WASH projects and their socio-cultural and structural factors influencing their involvement in Misungwi and Magu districts, Mwanza Region, Tanzania. Methodology: An exploratory qualitative study design was employed. Data were collected through Focus Group Discussions and Key Informant Interviews with key stakeholders involved in WASH projects. Verbatim transcription and thematic analysis were conducted, and a participation scorecard was used to assess the level of women’s participation in WASH-related activities and decision-making processes. Results: The study found that women’s participation in WASH projects was largely passive and often contingent upon men’s decisions. Cultural norms, household power hierarchies, and the requirement for permission from husbands or male family members significantly constrained women’s active involvement in decision-making. As a result, women’s roles were frequently limited to implementation rather than leadership roles. Conclusion: Women’s participation in WASH projects in the study area remains constrained by entrenched socio-economic inequalities and patriarchal cultural norms. Addressing these barriers requires comprehensive strategies that promote women’s economic empowerment, challenge restrictive gender norms, and recognize household power dynamics. Policies and programs that intentionally strengthen women’s decision-making authority are critical for achieving equitable and sustainable WASH outcomes.